Generic green skills: industry and perspectives on technical education and vocational training (TVET) - Abd. Zolkifli, Mohd. Hamid (RAVTE, 2016)
The development of green technology has intensified in the early 21st century as evident by the increasing attention given to it by governments and industries. This development requires more employees who possess generic green skills. Questions on what generic green skills are, is still unclear and needs further investigation. This qualitative study explored the perspective of employers and academicians about the meaning of generic green skills. Interviews with ten personnel (three from industries currently involved in green practices and seven academicians from the Department of Technical and Engineering Education, Faculty of Education, Universiti Teknologi Malaysia were conducted from January to May 2015. Results indicate that employers and academicians are fully aware of the importance of environmental sustainability. Although some were found to be ignorant about the term generic green skills, they showed an inclination towards referring to generic green skills as green practices. To achieve change, emphasis should be placed on the role of technical education and vocational training (TVET) in developing generic green skills which can eventually lead to environmental sustainability. Therefore, TVET could serve as an effective platform in promoting generic green skills. Findings of this study are just the initial step in exploring what generic green skills are. More studies should be conducted to better understand and stimulate the inclusion of generic green skills in all industries, including green technology-oriented industry to further improve awareness and implementation practices among the parties concerned.